Modeling of austenite formation kinetics of dual-phase steel during continuous annealing process - Xianbang Dong; Yuwen Zhang; Jiang Chang; Changhui Yuan; Daojun Ni; Yonggang Yang; Zhenli Mi (Materials Research Express)
In this work, a mixed model was used to achieve high-precision prediction of austenite kinetics during continuous annealing. The effects of annealing temperature and holding time on volume fraction of austenite were studied by continuous heating and holding treatments in the intercritical region. A Johnson–Mehl–Avrami–Kolmogorov (JMAK) based austenite formation kinetics model was established, and the volume fraction of austenite during the actual continuous annealing process was predicted. The results indicate that with the increase of annealing temperature and holding time, the volume fraction of austenite of dual-phase (DP) steel gradually increases with a value of 49.9% at 805 °C for 132 s. In addition, the theoretical calculation results of the model are consistent with the experimental results, which verifies the effectiveness of the established model. The model prediction accuracy is above 95%, which provides a reliable basis for optimizing the continuous annealing process parameters of DP steel.